Selective Androgen Receptor Modulators - A Review of Potential Uses, Benefits, Side effects and Limitations - Kamil Ostafin; Krzysztof Edyko; Piotr Petryla; Mikołaj Minkner; Borys Bienkowski; Krzysztof Feja; Zuzanna Suwała; Natalia Rektor; Ewa Łuczak; Urszula Marchewka (Kazimierz Wielki University, 2023)
Introduction: Selective Androgen Receptor Modulators (SARMs) are a group of chemical compounds capable of selectively activating androgen receptors (ARs) in the body. These substances can play a significant role in a new therapeutic approach in various fields of medicine, limiting the side effects associated with traditional anabolic steroids. In this article, we will focus on an overview of the current scientific knowledge on SARMs, their mechanisms of action, potential therapeutic applications, risks and challenges related to their use.  Aim of the study: The primary aim of this study was to to present potential use of selective androgen receptor modulators in sport and treatment focusing on its benefits and limitations as well as side effects aspects.  State of Knowledge:  SARMs in research show therapeutic benefits in the treatment of diseases such as osteoporosis, benign prostatic hyperplasia, muscle diseases and some types of cancer. Some studies suggest that few SARMs may be hepatotoxic. Most research on SARMs has been short-term, so the long-term effects of their use remain poorly understood.  Conclusion: The popularity of SARMs is constantly growing, and research on their use in medicine and sports provides more and more new ways to use them. Despite promising results, these compounds still pose many scientific challenges and raise legitimate concerns about their long-term effects on human health.